Encountering the Elements Horizon, Materiality and Temporal Perspectives in Contemporary Landscape Representations - Somhegyi, Zoltán (Aesthetica Preprint, 2024)
In this paper I am curious of the aesthetic investigation of some of the most elemental and essential constituents of landscape representations, that are, at the same time, also among the basic coordinates in our existence in the world. More precisely, I would like to survey some aspects of the artistic explorations of the horizon, material(ity) and time, through four contemporary artists’ pieces, those by Hiroshi Sugimoto, Taiji Matsue, Levente Baranyai and Torben Eskerod. As it will be clear, their series of artworks can be considered as aesthetically captivating investigations – not only artistic but philosophical investigations – into space, matter and time. The pieces are thus meditations on the perception of some of the fundamental elements of human condition, and the creative survey of these by the contemporary artists provide the observer with particular insights that can be gained only through works, and that would have otherwise been, most likely, undiscovered.